Estrategias pedagógicas efectivas para la inclusión de Estudiantes de primaria en el aula regular: Un análisis sistemático en principales países de latinoamérica (2024)
This research systematically addresses effective pedagogical strategies for the inclusion of elementary school students in regular classrooms in the main Latin American countries, based on studies published between 2013 and 2023.This project uses a qualitative methodology with a hermeneutic approach and descriptive design.